The effect of algorithm teaching on the problem-solving skills of deaf-hard hearing students. Issue 4 (7th November 2017) - Deveci Topal, Arzu; Çoban Budak, Esra; Kolburan Geçer, Aynur
Abstract : Purpose: The purpose of this paper is to identify the effects of algorithm teaching on the problem-solving skills of deaf-hard hearing students. Design/methodology/approach: In this research, a pre-test and post-test problem-solving scale was applied to the single group (16 deaf-hard hearing students at a secondary school level) that had received algorithm education. Pre-test and post-test results were compared in order to see whether there was a significant difference among students in terms of their problem-solving attitudes. Students' levels of performing the applications were examined through observation forms and their opinions about algorithm teaching were received. Findings: As a result of the research, it was determined that implemented algorithm teaching had a significant effect on improving the problem-solving skills of the students. Originality/value: Scratch training can be administered as either a compulsory or an optional course for hearing students as the Scratch programme offers the opportunity of teaching algorithmic reasoning with games, making the courses entertaining and giving students the chance to create their own designs which helps to improve their creative problem-solving skills and their motivation accordingly. Scratch teaching can be beneficial in developing students' problem-solving behaviours and creativity.